Tadbir and Adab as Constitutive Elements of Management: A Framework for an Islamic Theory of Management - Ismail, Mohd Zaidi (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Tadbir and Adab as Constitutive Elements of Management: A Framework for an Islamic Theory of Management